Medicinal Importance of Flavonoid “Eupatorin” in the Health Sectors: Therapeutic Benefit and Pharmacological Activities Through Scientific Data Analysis - Patel, Dinesh K. (Current Chinese Science, 2021)
Background: Herbal medicines have been used in the health sector for the treatment of human disorders from the ancient time till the modern age. Plant based herbal products have an important place in medicine due to their health beneficial potential and pharmacological activities. Traditional medicines have been used in developing country, such as India to the developed countries such as the USA and Europe. Traditional medicines have been used in the health sectors for the treatment of numerous types of human disorders. Phytoconstituents play an important role in the growth, reproduction and development of the human being. Plant products have been used for the treatment of skin disorders, wounds, and various forms of inflammatory diseases. Flavonoids are a colorful component of fruits, seeds, vegetables, nuts and plants. Flavonoids have been used for the treatment of human disorders due to their vast pharmacological activities. Methods: Scientific information on eupatorin has been collected from different literature sources and analyzed in order to know the health benefit of eupatorin in medicine. All the scientific information presented here is collected from various databases such as Google, PubMed, and Science Direct etc. Pharmacological activity data of eupatorin have been collected from various literature databases and analyzed here to know the beneficial health potential of eupatorin in medicine. However, important analytical tools for the separation, isolation and identification of eupatorin have also been discussed in the present paper. Results: Eupatorin (39,5-dihydroxy-49,6,7-trimethoxyflavone) is a flavone class flavonoidal compound found to be present in the Orthosiphon stamineus, Salvia mirzayanii, Lantana montevidensis, Lantana montevidensis and Tanacetum vulgare. Eupatorin have been used against bronchitis, stomach disorders and various forms of cancer. Eupatorin have a potential role in various cancerous disorders, such as human uterus carcinoma, human gastric adenocarcinoma, breast carcinoma, melanoma and colon carcinoma. Pharmacological data analysis revealed the effectiveness of eupatorin in human cancer and various types of inflammatory disorders. However, the effectiveness of eupatorin against microorganism and enzymes were also presented in the present work with their herbicidal and vasorelaxation potential in the medicine. Eupatorin has a valuable role in the development of adjuvant chemotherapeutic agents. Conclusion: Present review will be beneficial to the researcher to understand the physiological importance of eupatorin in medicine for the development of newer and effective medicine.
Keywords: favonoid